DNA Damage Induced by Alkylating Agents and Repair Pathways. (19th October 2010) - Kondo, Natsuko; Takahashi, Akihisa; Ono, Koji; Ohnishi, Takeo
Abstract : The cytotoxic effects of alkylating agents are strongly attenuated by cellular DNA repair processes, necessitating a clear understanding of the repair mechanisms. Simple methylating agents form adducts atN - andO -atoms.N -methylations are removed by base excision repair, AlkB homologues, or nucleotide excision repair (NER).O 6 -methylguanine (MeG), which can eventually become cytotoxic and mutagenic, is repaired byO 6 -methylguanine-DNA methyltransferase, andO 6 MeG:T mispairs are recognized by the mismatch repair system (MMR). MMR cannot repair theO 6 MeG/T mispairs, which eventually lead to double-strand breaks. Bifunctional alkylating agents form interstrand cross-links (ICLs) which are more complex and highly cytotoxic. ICLs are repaired by complex of NER factors (e.g., endnuclease xeroderma pigmentosum complementation group F-excision repair cross-complementing rodent repair deficiency complementation group 1), Fanconi anemia repair, and homologous recombination. A detailed understanding of how cells cope with DNA damage caused by alkylating agents is therefore potentially useful in clinical medicine.